2021
DOI: 10.1186/s40900-021-00261-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community engaged research experiences and preferences: a multi-level qualitative investigation

Abstract: Background Community engagement may make research more relevant, translatable, and sustainable, hence improving the possibility of reducing health disparities. The purpose of this study was to explore strategies for community engagement adopted by research teams and identify areas for enhancing engagement in future community engaged research. Methods The Community Engagement Program of the Johns Hopkins Institute for Clinical and Translational Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Could this same principle also apply to community engagement? As Han 2021 has highlighted [ 11 ], this is an evolving area for community engagement. As part of the final phase of the Alliance work a formal evaluation of the CAG is planned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Could this same principle also apply to community engagement? As Han 2021 has highlighted [ 11 ], this is an evolving area for community engagement. As part of the final phase of the Alliance work a formal evaluation of the CAG is planned.…”
Section: Discussionmentioning
confidence: 99%
“…Being engaged can increase overall genetic literacy as guidance is provided on implementation, transparency, and quality and trustworthiness of policies and service delivery programs [ 10 ]. At the same time, it is important to understand patients’ and communities’ experiences of engagement, both in research and in health service delivery [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…MOUs are a means of documenting and formalising the intentions and general expectations of all parties. Our research programme is strongly involved with and contributes to the Newcomer Research Network (NRN) at the University of Calgary 28. The NRN has signed an MOU with several organisations with whom we have been doing research, specifically ISPOs, which has been deemed useful both by the organisations and academics.…”
Section: From Engagement To Partnershipmentioning
confidence: 99%
“…Researchers often partner with organisations on research with immigrant/ethnic-minority communities; however, often the organisation’s role remains limited to providing access to community members for data collection through their community contacts or the partnership tends to be more confined for knowledge translation. While a truly community-engaged approach involving mutual connection, understanding and engagement among researchers and the community is ideal, most research does not involve this level of partnership 28. The belief is that researchers tend to commodify and capitalise research on immigrant/ethnic-minority populations rather than channel it towards actually improving or empowering communities.…”
Section: Partnership Learningsmentioning
confidence: 99%
“…17,18 CER has been widely recognized in research as imperative to reduce health disparities. 19-21 Use of CER within qualitative research can enhance translational results. Previous research has found that studies incorporating a CER approach has a positive impact on health behaviors including diet, exercise, and health outcomes (i.e.…”
mentioning
confidence: 99%